The incidence of the lack of documentary contribution in the concession of nationality by residence: the Messaoud case E sther Gómez Campelo - Gómez Campelo, Esther (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The judgment of the Supreme Court that recognizes the right to Spanish nationality by residence is analyzed, after the positive assessment of good civic conduct despite lacking the documentation required for its accreditation. It is the global weighting of the various personal circumstances that concur that must make the competent authority conceive a well-founded conviction about the requirement and not a rigid assessment of the regulatory requirements on the documentation to be presented. The interrelation between good civic conduct and the lack of criminal and/or police records is also analyzed.